The use of the SF-36 questionnaire in adult survivors of childhood cancer: evaluation of data quality, score reliability, and scaling assumptions - Winter David L (Health and Quality of Life Outcomes, 2006)
Abstract Background The SF-36 has been used in a number of previous studies that have investigated the health status of childhood cancer survivors, but it never has been evaluated regarding data quality, scaling assumptions, and reliability in this population. As health status among childhood cancer survivors is being increasingly investigated, it is important that the measurement instruments are reliable, validated and appropriate for use in this population. The aim of this paper was to determine whether the SF-36 questionnaire is a valid and reliable instrument in assessing self-perceived health status of adult survivors of childhood cancer. Methods We examined the SF-36 to see how it performed with respect to (1) data completeness, (2) distribution of the scale scores, (3) item-internal consistency, (4) item-discriminant validity, (5) internal consistency, and (6) scaling assumptions. For this investigation we used SF-36 data from a population-based study of 10,189 adult survivors of childhood cancer. Results Overall, missing values ranged per item from 0.5 to 2.9 percent. Ceiling effects were found to be highest in the role limitation-physical (76.7%) and role limitation-emotional (76.5%) scales. All correlations between items and their hypothesised scales exceeded the suggested standard of 0.40 for satisfactory item-consistency. Across all scales, the Cronbach's alpha coefficient of reliability was found to be higher than the suggested value of 0.70. Consistent across all cancer groups, the physical health related scale scores correlated strongly with the Physical Component Summary (PCS) scale scores and weakly with the Mental Component Summary (MCS) scale scores. Also, the mental health and role limitation-emotional scales correlated strongly with the MCS scale score and weakly with the PCS scale score. Moderate to strong correlations with both summary scores were found for the general health perception, energy/vitality, and social functioning scales. Conclusion The findings presented in this paper provide support for the validity and reliability of the SF-36 when used in long-term survivors of childhood cancer. These findings should encourage other researchers and health care practitioners to use the SF-36 when assessing health status in this population, although it should be recognised that ceiling effects can occur.